Development and Implementation of a Psychological Service for Patients With Cancer. Issue 3 (August 2020) - Yusufov, Miryam; Grebstein, Lawrence; Rossi, Joseph S.; Redding, Colleen A.; Ferszt, Ginette G.; Prochaska, James O.
Abstract: Cancer patients frequently experience considerable distress during diagnosis and treatment. The aims of this study were to describe the development and utilization of a psychological service for cancer patients at a community hospital—and to provide preliminary results on clinical outcomes in a "real-world" clinical setting. This program was developed collaboratively by individuals from a university-based clinical psychology doctoral program and a community hospital. The psychological service was comprised of a licensed, PhD-level clinical psychologist and seven clinical psychology doctoral students. Patients were typically referred by their oncologists or nurses. Distress, depression, and anxiety were evaluated for a small subsample of participants. From the time the program was initiated, 238 patients between ages 18 and 95 (M = 66.4) were evaluated over a 3-year period. Most patients (77.8%) were offered psychosocial care. Although 49.8% declined treatment, 23.6% attended one session and 26.6% attended two or more. Average number of individual sessions was 2.77 (SD = 8.31, range = 0-96) and 0.06 (SD = 0.43, range = 0-4) for groups sessions. Patients referred through the Survivorship Training and Rehabilitation (STAR) Program® (i.e., a program providing multidisciplinary services) were more likely to engage in psychosocial care than those who found out about behavioral health in other ways. Patients experienced declines in depression (Wilks' Λ = .580, F(2, 14)=5.08, p = .022), but not anxiety (Wilks' Λ = .613, F(2, 12)=3.79, p = .053) across sessions. Two in-depth case descriptions are provided. Distress tracking may be improved if nurses, oncologists, and behavioral health providers administer measures. Partnerships between clinical psychology doctoral programs and hospitals may be mutually beneficial – and may advance the dissemination and implementation of evidence-based psychosocial interventions. Hospitals offering cancer treatment may benefit from generating referrals for comprehensive cancer care. These efforts can serve as a model for other hospitals seeking to integrate behavioral health into routine cancer treatment. Highlights: Married patients were less likely to accept psychological treatment. Employed patients were less likely to accept psychological treatment. Providing "bedside" psychological treatment may minimize barriers. Clinical psychology programs should partner with hospitals to increase treatment dissemination. These partnerships may be mutually beneficial for trainees and patients.